Design, Synthesis and Biological Evaluation of Aromatase Inhibitors Based on Sulfonates and Sulfonamides of Resveratrol - Marialuigia Fantacuzzi; Marialucia Gallorini; Nicola Gambacorta; Alessandra Ammazzalorso; Zeineb Aturki; Marwa Balaha; Simone Carradori; Letizia Giampietro; Cristina Maccallini; Amelia Cataldi; Orazio Nicolotti; Rosa Amoroso; et al. (MDPI AG, 2021)
A library of sulfonate and sulfonamide derivatives of Resveratrol was synthesized and tested for its aromatase inhibitory potential. Interestingly, sulfonate derivatives were found to be more active than sulfonamide bioisosteres with IC50 values in the low micromolar range. The sulfonate analogues 1b-c and 1j exhibited good in vitro antiproliferative activity on the MCF7 cell line, evidenced by MTT and LDH release assays. Structure-activity relationships suggested that electronic and lipophilic properties could have a different role in promoting the biological response for sulfonates and sulfonamides, respectively. Docking studies disclosed the main interactions at a molecular level of detail behind the observed inhibition of the more active compounds whose chemical stability has been evaluated with nano-liquid chromatography. Finally, 1b-c and 1j were highlighted as sulfonates to be further developed as novel and original aromatase inhibitors.